RUBIC (ReproUnion Biobank and Infertility Cohort): A binational clinical foundation to study risk factors, life course, and treatment of infertility and infertility‐related morbidity. (18th June 2021) - Priskorn, Lærke; Tøttenborg, Sandra Søgaard; Almstrup, Kristian; Andersson, Anna‐Maria; Axelsson, Jonatan; Bräuner, Elvira Vaclavik; Elenkov, Angel; Freiesleben, Nina la Cour; Giwercman, Yvonne Lundberg; Grøndahl, Marie Louise; Hansen, Ann Holm; Hansen, Laura Smidt; et al.
Abstract: Background: Infertility affects 15%–25% of all couples during their reproductive life span. It is a significant societal and public health problem with potential psychological, social, and economic consequences. Furthermore, infertility has been linked to adverse long‐term health outcomes. Despite the advanced diagnostic and therapeutic techniques available, approximately 30% of infertile couples do not obtain a live birth after fertility treatment. For these couples, there are no further options to increase their chances of a successful pregnancy and live birth. Objectives: Three overall questions will be studied: (1) What are the risk factors and natural life courses of infertility, early embryonic loss, and adverse pregnancy outcomes? (2) Can we develop new diagnostic and prognostic biomarkers for fecundity and treatment success? And (3) what are the health characteristics of women and men in infertile couples at the time of fertility treatment and during long‐term follow‐up? Material and Methods: ReproUnion Biobank and Infertility Cohort (RUBIC) is established as an add‐on to the routine fertility management at Copenhagen University Hospital Departments in the Capital Region of Denmark and Reproductive Medicine Centre at Skåne University Hospital in Sweden. The aim is to include a total of 5000 couples equally distributed between Denmark and Sweden. The first patients were enrolled in June 2020. All eligible infertile couples are prospectively asked to participate in the project. Participants complete an extensive questionnaire and undergo a physical examination and collection of biospecimens (blood, urine, hair, saliva, rectal swabs, feces, semen, endometrial biopsies, and vaginal swabs). After the cohort is established, the couples will be linked to the Danish and Swedish national registers to obtain information on parental, perinatal, childhood, and adult life histories, including disease and medication history. This will enable us to understand the causes of infertility and identify novel therapeutic options for this important societal problem.